Apakah Mendengarkan Murrotal Al-Quran Dapat Menurunkan Kecemasan Akademik Pada Mahasiswa? - Azmul Fuady Idham; Andi Ahmad Ridha (JIP (Jurnal Intervensi Psikologi), 2017)
Academic anxiety is often experienced by each individual. One of the methods used in lowering academic anxiety is to listen murottal Quran. This study aimed to test the effectiveness of listening murottal Quran in reducing anxiety in students. Respondents were selected using random sampling techniques using the design of experiment one group pretest-posttest. The subject of this research were 21 students of the faculty of Psychology University of Makassar class of 2015. This study uses academic anxiety scale of Isthifha (2011). The results of this study showed that listening to the Quran murottal effective in reducing anxiety in a student's academic. This study provides a new alternative to students who often have academic anxiety by listening murottal Quran.Keywords: Murottal Quran; Academic Anxiety; Students